Kemampuan Pemecahan Masalah Berdasarkan Kemampuan Awal Antara Problem Based Learning Dan Case Based Learning - Husen Bajri, Salamun; Gunadi, Farid; Wiwit Damayanti Lestari (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
The study aims to identify differences in problem-solving skills between students who have acquired the methodology of Problem Based Learning and Case Based Learning based on the level of initial mathematical skills. This research was carried out in MAN 1 Indramayu academic year 2023-2024. The research was conducted in two classes, X-4 and X-7. Instruments in this research there are two instruments namely instruments to measure the level of initial mathematical ability and instruments for measuring the ability to solve problems of students material opportunity. The analysis method in this study uses two-way/factor variance analysis (2x2) by level. Before doing the calculations using ANOVA two-way/factor, the author performed the normality test using Kolmogorov-Smirnov and the homogeneity test with the bartlett test. Obtain the result that there is a difference in problem-solving skills based on the level of initial mathematical skills of students who acquire the Problem Based Learning method with Case Based Learning. Keyword: Problem Based Learning, Case Based Learning, Problem Solving Skills, Early Mathematic Skills